Sounding Extremes: Ecological Sound Art in the Anthropocene - Barclay, Leah (Circuit, 2022)
The catastrophic impacts of climate change, vanishing biodiversity, and the rapid deterioration of our global ecosystems require urgent attention and aggressive political action. This article explores a body of interdisciplinary research through a series of ecological sound projects designed to draw attention and awareness to changing ecosystems. These projects are framed as participatory acoustic ecology and position the discipline as a socially engaged, inclusive, accessible, interdisciplinary field that inspires communities to listen and act during times of crisis.